K‐Birnessite Electrode Obtained by Ion Exchange for Potassium‐Ion Batteries: Insight into the Concerted Ionic Diffusion and K Storage Mechanism. Issue 1 (31st October 2018) - Gao, Ang; Li, Min; Guo, Nannan; Qiu, Daping; Li, Yan; Wang, Senhao; Lu, Xia; Wang, Feng; Yang, Ru
Abstract: Novel and low‐cost rechargeable batteries are of considerable interest for application in large‐scale energy storage systems. In this context, K‐Birnessite is synthesized using a facile solid‐state reaction as a promising cathode for potassium‐ion batteries. During synthesis, an ion exchange protocol is applied to increase K content in the K‐Birnessite electrode, which results in a reversible capacity as high as 125 mAh g −1 at 0.2 C. Upon K + exchange the reversible phase transitions are verified by in situ X‐ray diffraction (XRD) characterization. The underlying mechanism is further revealed to be the concerted K + ion diffusion with quite low activation energies by first‐principle simulations. These new findings provide new insights into electrode process kinetics, and lay a solid foundation for material design and optimization of potassium‐ion batteries for large‐scale energy storage. Abstract : K‐Birnessite material is investigated as a promising cathode for potassium‐ion batteries by both first‐principle calculations and experimental characterizations. It is found that there is concerted K + ion diffusion behavior that accounts for this superior electrochemical performance, which provides new insights into electrode process kinetics, and lays a solid foundation for material design and optimization of potassium‐ion batteries.